Experimental evaluation of a modified direct evaporative cooling system combining luffa fiber—charcoal cooling pad and activated carbon dehumidifying pad - T. O. Ahmadu; Y. S. Sanusi; F. Usman (Journal of Engineering and Applied Science, 2022)
Abstract Evaporative cooling technology has a potential to serve as a substitute to conventional vapor compression cooling. Direct evaporative cooling however usually introduces more moisture to the cooling space. In this study, the performance of a modified direct evaporative cooling system that combines a cooling pad and a removable dehumidifying pad has been experimentally evaluated for space cooling. The cooling pad is made of luffa fiber lagged with charcoal, while the dehumidifying pad is made of activated carbon derived from tamarind seed. Results for two experimental days, which span from 8:30 am to 5:30 pm each day are reported in this work. The peak cooling load requirement of the room was evaluated as 4.53 kW. On the first experimental day, in which the dehumidifying pad was removed from the system, results indicated a minimum room temperature of 24 oC was achieved, which resulted in a maximum temperature drop of 11 oC from ambient temperature. However, indoor relative humidity increased to a maximum of 84%, while outdoor relative humidity was 30%. The dehumidifying pad was used on the second experimental day. Results from the second experimental day showed a minimum room temperature of 26.5 oC was achieved, resulting in a maximum temperature drop of 10 oC from ambient. Maximum indoor relative humidity recorded was 49%, while the outdoor relative humidity was 34%, an indication that the dehumidifying pad was able to absorb moisture from the cooled air. Maximum cooling capacity, efficiency, and COP of 3.84 kW, 84.6% and 16.1 respectively were achieved by the system without the dehumidifying pad. Corresponding values of 3.2 kW, 71.4% and 13.4 respectively were recorded when the system was operated with the dehumidifying pad.